Distribution of organic-walled dinoflagellate cysts in surface sediments of San Matías Gulf (North Patagonian Shelf, Argentina): a seed bank for potential harmful algal blooms - Xillovich, Juan B.; Borel, C. Marcela; Ferronato, Carola; Krock, Bernd (Frontiers in Marine Science, 2025)
In the southwestern Atlantic Ocean, the San Matías Gulf (SMG) is a semi-enclosed coastal ecosystem (40.5°-42.5°S; 63.5°-65.5°W) with considerably greater depths (up to 190 m) than the adjacent continental shelf ( 70 m). A thermohaline frontal system develops in a latitudinal position around 41.8°S from spring to summer leading to high biological productivity in this relevant area for fisheries. In this study, twelve surface sediment samples from the SMG were analyzed for the determination of species and distribution of organic-walled dinoflagellate cysts (dinocysts) in relation to physico-chemical conditions (grain-size of sediments, water column stability, spring sea-surface temperature, salinity, and nitrate concentration). Thirty different taxa of dinocysts were recorded, of which twenty-eight were identified to species level. The strong dominance of Operculodinium centrocarpum (cyst of Protoceratium reticulatum, a yessotoxin producer in the Argentine Sea) accompanied by minor abundances of other phototrophic and heterotrophic taxa characterized all assemblages. Cysts of Alexandrium catenella, which is known as a saxitoxin-producing species in the gulf, were also recorded across sites. The highest absolute abundances of dinocysts occurred at the inner gulf, north of the latitudinal front. For this area we argue that multi-year fluxes of phototrophic dinocysts to the silty bottom are enhanced by the great production of vegetative cells in the seasonally stratified water column, the encystment strategies of the dominant species and the particular physical oceanographic characteristics. Although densities of both phototrophic and heterotrophic cysts were lower in the coarser sediments near the mouth of the gulf, the relative abundances of heterotrophic cysts were higher. The preference of heterotrophic species reflects higher nitrate concentrations, which increase the primary production and thus food availability for heterotrophs.